Town of Goombungee, Parish of Goombungee - Queensland. Department of Mapping and Surveying (Brisbane : Dept. of Mapping and Surveying, 1981)
Shows streets, block and sections, and cadastral information.
Keywords: Real property -- Queensland -- Goombungee -- Maps; Goombungee (Qld.) -- Maps